Media Huruf Magnet terhadap Kemampuan Menulis Huruf Vokal pada Anak-Anak Disabilias Intelektual Sedang - Ani Rohmawati; Nostalgianti Citra Prystiananta; Lailil Aflahkul Yaum (JOEAI (Journal of Education and Instruction), 2026)
This study aims to determine the effect of magnetic letters on the vowel writing skills of seventh-grade children with moderate intellectual disabilities at SLB C TPA Jember. The study used a Single Subject Research (SSR) with an A-B design, involving one subject. Data collection was implemented in the form of a practical test over 15 sessions, including 5 baseline sessions and 10 intervention sessions. The results showed that the percentage of ability in the baseline phase ranged from 42%–61% with a mean level of 52.6%. After the intervention using magnetic letters, the percentage changed to 93% with a mean level of 77.2%. The overlap percentage of 0% indicates that the intervention had a positive effect on the development of vowel writing skills in children with moderate intellectual disabilities at SLB C TPA Jember.   Keywords: Intellectual Disability, Vowels, Magnet Letters, Writing